Curing Kinetics of Hybrid Networks Composed of Benzoxazine and Multifunctional Novolac Epoxy - Wu Ke; Wang Rumin; Zeng Jinfang (International Journal of Polymer Science)
A novel hybrid network composed of benzoxazines (BZ) and novolac epoxy resin (F-51) was prepared successfully. Thermal properties, curing kinetics, and decomposition process were studied using isothermal differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) in this paper. The reactive mechanism of F-51/BZ mixture system is different from the BZ homopolymers at low temperatures; two resin systems follow the autocatalytic model mainly at high temperatures. Thermogravimetric analysis indicates that F-51 can have no significant effect on thermal degradation temperatures and on increasing char yield.